High-Dose Chemotherapy with Stem Cell Rescue in Desmoplastic Small Round Cell Tumor: A Single-Institution Experience and Review of the Literature. (6th May 2018) - Bailey, Kayleen; Roth, Michael; Weiser, Daniel; Gill, Jonathan
Abstract : Purpose . Desmoplastic small round cell tumor (DSRCT) is a rare cancer that predominantly affects males averaging 21 years of age at the time of diagnosis. We describe four cases from our institution and place them within the context of a comprehensive review of the literature. Patients and Methods . Study population included any patient who received treatment at Children's Hospital at Montefiore (CHAM) with histologic diagnosis of DSRCT. A search of the electronic databases PubMed, Cochrane Central Register of Controlled Trials, MEDLINE, and EMBASE for the terms "desmoplastic" AND "small" AND "round" AND "cell" AND "tumor" was performed. Results . One CHAM patient died of disease at 39 months, one patient has relapsed disease at 40 months, and two patients have no evidence of disease at 60 and 91 months. In the literature review, the 3-year OS was 36% and 5-year OS was 13%. There was a statistically significant difference in OS between no transplant and SCT in remission (p = 0.004 ); however, there was no difference between no transplant and SCT not in remission (p = 0.23 ). Conclusion . Given the poor prognosis in DSRCT, this study supports further prospective research into the possible benefit of consolidation of autologous SCT in patients with DSRCT who are in remission, with the alternative inference that these patients in remission may fare well without SCT. Our retrospective review of the literature does not support SCT for patients who are not in remission.